Educação patrimonial: o hino municipal de Nova Palma como referência pedagógica do patrimônio local - Pesamosca, Simone Osmari Lago (2024)
This dissertation is the result of research developed with the Postgraduate Program in Cultural Heritage at the Universidade Federal de Santa Maria, within the Area of Concentration and the History and Cultural Heritage Research Line. The research comes from a professional trajectory that seeks to contribute to local and regional development through work with Heritage Education in public schools in Nova Palma, a city in the Geopark Quarta Colônia - UNESCO. The study addresses theoretical aspects that support the importance of Heritage Education as a teaching tool to work on the theme of cultural heritage in the different curricular components. Furthermore, during the study, the lack of specific teaching materials for this purpose was verified, so teaching support material was created that will contribute to teaching practices. The material prepared is composed of two parts: the first presents theoretical concepts that will enable teachers to increase their knowledge about the importance of working with Heritage Education through a critical stance towards the importance of this topic; the second stage, in turn, presents a sequence of activities, based on the Municipal Anthem of Nova Palma, aimed at the final years (6th to 9th year) of elementary school. Although the stages are directed, the material can be applied to other stages of the public education network in Nova Palma. In this way, Heritage Education will contribute significantly to the development of a more promising and critical society, in which students can play a leading role in safeguarding local heritage, ensuring that it can be known, preserved, enjoyed, and bequeathed to future generations, all from a local and regional development perspective.